2002
DOI: 10.1046/j.1526-100x.2002.00129.x
|View full text |Cite
|
Sign up to set email alerts
|

Forest Restoration Treatment Effects on the Nesting Success of Western Bluebirds (Sialia mexicana)

Abstract: We examined the effects of presettlement forest restoration treatments on the nesting success of Western Bluebirds in ponderosa pine forests of northwestern Arizona, U.S.A. From 1998 to 2001 we monitored 97 active Western Bluebird nests, 41 in current‐condition untreated forest and 56 in restoration‐treated forest. We found no effect of restoration treatments on clutch size and little effect on the number of nestlings per nest. However, in treated forest stands number of fledglings per nest averaged 1.6 times … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
26
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(26 citation statements)
references
References 24 publications
(24 reference statements)
0
26
0
Order By: Relevance
“…Battin (2003) found an increase in fledging success for plumbeous vireos (Vireo plumbeus) and western tanagers (Piranga ludoviciana) within 4 years of treatment in thin/burn versus untreated areas. Germaine and Germaine (2002) found thinning and burning treatments had little effect on the number of eggs or nestlings per nest of western bluebirds within 5 years of treatment, but were associated with a higher number of fledglings per nest and greater probability of fledging at least one young compared to controls. They also found a higher incidence of parasitic infestations by blowflies in nests in thin/burn treatments compared to controls (Germaine and Germaine, 2002).…”
Section: Reproductive Outputmentioning
confidence: 81%
See 1 more Smart Citation
“…Battin (2003) found an increase in fledging success for plumbeous vireos (Vireo plumbeus) and western tanagers (Piranga ludoviciana) within 4 years of treatment in thin/burn versus untreated areas. Germaine and Germaine (2002) found thinning and burning treatments had little effect on the number of eggs or nestlings per nest of western bluebirds within 5 years of treatment, but were associated with a higher number of fledglings per nest and greater probability of fledging at least one young compared to controls. They also found a higher incidence of parasitic infestations by blowflies in nests in thin/burn treatments compared to controls (Germaine and Germaine, 2002).…”
Section: Reproductive Outputmentioning
confidence: 81%
“…Germaine and Germaine (2002) found thinning and burning treatments had little effect on the number of eggs or nestlings per nest of western bluebirds within 5 years of treatment, but were associated with a higher number of fledglings per nest and greater probability of fledging at least one young compared to controls. They also found a higher incidence of parasitic infestations by blowflies in nests in thin/burn treatments compared to controls (Germaine and Germaine, 2002). Wightman and Germaine (2006) found that successful western bluebird nests, determined by number of young in the nest on the last day prior to fledge, were associated with increased understory and bare ground and lower conifer tree densities found in thinned and burned treatments 7 years post-treatment.…”
Section: Reproductive Outputmentioning
confidence: 81%
“…Despite these calls, the number of 71 studies of restoration effects on vertebrates is still low and most of them focus on birds in forests 72 and shrubs (e.g. Brawn, 1998;Germaine and Germaine, 2002;Hoover, 2008;Machmer, 2002). 2001) and pollination (Vieira et al, 2009).…”
mentioning
confidence: 99%
“…Previous studies have shown short-term (1-3 years) neutral to positive responses of avian communities and many species to fire and fire surrogate treatments in dry forest (Germaine and Germaine, 2002;Zebehazy et al, 2004;Wightman and Germaine, 2006;Gaines et al, 2007). Our study contributes to this knowledge base by providing managers with information on the foraging response of bark gleaners to these treatments.…”
Section: Discussionmentioning
confidence: 72%